A descriptive case study on the interplay of levers of control framework and innovation - Barros, R. S.; Ferreira, A. (XVII Grudis Conference and Doctoral Colloquium, 2018)
A recent research stream has emphasized that management control systems (MCS) do not have the negative effect that has been associated with control in the more traditional literature. In this change, Simons’ framework has played a preponderant role, in which the nature of the relationship between each lever and innovation is explored. However, an important aspect of the framework that has been somehow neglected from the literature is the need for balance within the four levers and the dynamic tensions that arise from their uses. In response, this study resorts to a case study approach in an innovative company to shed some light on how organizations attempt to balance their MCS packages within the four Simons’ levers concerning the innovative effort and how the dynamic tensions they create contributes to it. In the case company, interactive systems present the most visible lever use, but notwithstanding, the other three levers are also present creating tensions within them. Diagnostic and boundary systems complement each other to create dynamic tension with the combined use of interactive and belief systems. With these dynamic tensions, managers can do more than balance innovation and the achievement of financial goals, ensuring that new developments take place in fields that are profitable. On one hand, diagnostic and boundary systems reduce the uncertainty associated with these developments and, on the other hand, interactive and belief systems create the favourable environment.